PSII-2 Effects of Replacing Supplemental Sucrose with Beef on Maternal Health and Fetal Growth and Development Using a Sow Biomedical Model. (7th December 2018) - Nelson, M; Ward, A; Swanson, K; Vonnahme, K; Berg, E
Abstract: Pregnant sows (Landrace x Yorkshire; BW = 222 kg; n = 21) were utilized to investigate substituting dietary sucrose with beef supplementation on maternal health and fetal development. A corn-soybean meal-based diet (CSM) was fed at one percent of BW at 700 h daily. Sows were randomly assigned to dietary supplement groups consisting of 126 g CSM (CON, n = 5); 110 g cooked ground beef (CGB; BEEF, n = 6); 54.8 g CGB and 42.7 g sucrose (B+S, n = 5); or 85.5 g sucrose (SUCROSE, n = 5). Dietary supplements were fed three times daily from d 40 to 110 (± 0.58) of gestation. Blood was collected from sows on d 29 (± 1.47) and 111 (± 0.58) of gestation. Sows were euthanized on d 111 (± 0.58) of gestation. Fetal growth measurements were recorded for all fetuses. Two median weight male and female fetuses were selected from each sow for tissue collections. A repeated measures design was modeled using MIXED procedure of SAS. Dietary treatment did not influence sow blood metabolites on d 29 and 111 of gestation (P = 0.09 and P = 0.20, respectively). Compared to CON and SUCROSE, BEEF fetuses had larger nose to crown lengths (6.03 and 6.02 ± 0.29 vs. 7.33 ± 0.36 cm, respectively; P = 0.04). Compared to CON, SUCROSE median weight fetuses had respectively larger BW (1296 ± 73.6 vs. 1556 ± 68.8 g; P = 0.02); heart girths (22.90 vs. 24.13 ± 0.40 cm; P = 0.03); and liver weights (36.48 ± 2.19 vs. 43.44 ± 2.05 g; P = 0.04). Dietary treatment did not influence other fetal characteristics or organ weights (P - 0.05). Gestational beef supplementation had minimal effects on maternal health or fetal growth; however, sucrose supplementation effects on fetal growth should be further explored.